Pre-Columbian land use in the ring-ditch region of the Bolivian Amazon. (August 2015) - Carson, John F; Watling, Jennifer; Mayle, Francis E; Whitney, Bronwen S; Iriarte, José; Prümers, Heiko; Soto, J Daniel
The nature and extent of pre-Columbian (pre-AD 1492) human impact in Amazonia is a contentious issue. The Bolivian Amazon has yielded some of the most impressive evidence for large and complex pre-Columbian societies in the Amazon basin, yet there remains relatively little data concerning the land use of these societies over time. Palaeoecology, when integrated with archaeological data, has the potential to fill these gaps in our knowledge. We present a 6000-year record of anthropogenic burning, agriculture and vegetation change, from an oxbow lake located adjacent to a pre-Columbian ring ditch in north-east Bolivia (13°15′44″S, 63°42′37″W). Human occupation around the lake site is inferred from pollen and phytoliths of maize ( Zea mays L.) and macroscopic charcoal evidence of anthropogenic burning. First occupation around the lake was radiocarbon dated to 2500 calibrated years before present (BP). The persistence of maize in the record from 1850 BP suggests that it was an important crop grown in the ring-ditch region in pre-Columbian times, and abundant macroscopic charcoal suggests that pre-Columbian land management entailed more extensive burning of the landscape than the slash-and-burn agriculture practised around the site today. The site was occupied continuously until near-modern times, although there is evidence for a decline in agricultural intensity or change in land-use strategy, and possible population decline, from 600–500 BP. The long and continuous occupation, which predates the establishment of rainforest in the region, suggests that pre-Columbian land use may have had a significant influence on ecosystem development at this site over the last 2000 years.